The apelin receptor influences biomechanical and morphological properties of endothelial cells. Issue 8 (26th February 2018) - Strohbach, Anne; Pennewitz, Malte; Glaubitz, Michael; Palankar, Raghavendra; Groß, Stefan; Lorenz, Florian; Materzok, Ilka; Rong, Alena; Busch, Mathias C.; Felix, Stephan B.; Delcea, Mihaela; Busch, Raila
Abstract : The adaption of endothelial cells to local flow conditions is a multifunctional process which leads to distinct alterations in cell shape, the subcellular distribution of structural proteins, and cellular function. G‐protein‐coupled receptors (GPCRs) have been identified to be fundamentally involved in such processes. Recently, we and others have shown that the expression of the endothelial GPCR apelin receptor (APJ) is regulated by fluid flow and that activation of APJ participates in signaling pathways which are related to processes of mechanotransduction. The present study aims to illuminate these findings by further visualization of APJ function. We show that APJ is located to the cellular junctions and might thus be associated with platelet endothelial cell adhesion molecule‐1 (PECAM‐1) in human umbilical vein endothelial cells (HUVEC). Furthermore, siRNA‐mediated silencing of APJ expression influences the shear‐induced adaption of HUVEC in terms of cytoskeletal remodeling, cellular elasticity, cellular motility, attachment, and distribution of adhesion complexes. Taken together, our results demonstrate that APJ is crucial for complemented endothelial adaption to local flow conditions. Abstract : The adaption of endothelial cells to local flow conditions is a multifunctional process which leads to distinct alterations in cell shape, the subcellular distribution of structural proteins, and cellular function. We show that siRNA‐mediated silencing of APJ expression influences the shear‐induced adaption of HUVEC in terms of cytoskeletal remodelling, cellular elasticity, cellular motility, attachment, and distribution of adhesion complexes.